Pendampingan Pengunaan Kemasan Yang Higienis di Desa Kambilo Kecamatan Wawo dalam Meningkatkan Penjualan - Sri Ernawati; Siti Fatimah; Nurul Mahmaantika; Dini Rahmadani; Fidiyatun Angriani (CV Putra Publisher, 2024)
Ethical assistance activities in doing business for turmeric MSMEs in Kampilo Village, Wawo District were carried out by Bima College of Economics (STIE) students. The aim of this activity is to provide understanding to turmeric business actors about the importance of ethics in business. Turmeric business actors in Kampilo village, Wawo sub-district do not yet know the importance of ethics in business in the businesses they run, one of which is that the turmeric business products they are selling now in the processing process do not meet standards in business ethics, for example, the turmeric drying process is carried out on the ground. only on a tarpaulin without caring about cleanliness and the condition of the surrounding environment. Apart from that, the process of packaging turmeric powder is only packaged using used bottles. Seeing this, we help by assisting in a more modern and attractive manufacturing and packaging process to help increase people's income in Kampilo village